2019
DOI: 10.1021/acs.jpcc.9b08648
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Photothermal Properties of Graphene Coated Au–Ag Hollow Nanoshells: A Modeling for Efficient Photothermal Therapy

Abstract: We study the optical and photothermal properties of graphene coated gold−silver alloy hollow nanoshells (Au−Ag HNSs) using the effective medium theory combined with the Pennes bioheat and Arrhenius equations. To increase the stability of Au−Ag HNSs in the presence of oxidants, acid, and heating, we propose the use of graphene as a protective shell on Au−Ag HNSs in photothermal therapy (PTT) applications. Calculating the extinction efficiency in tumor tissue, we show that the surface plasmon resonant (SPR) peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…where x denotes the Au molar fraction in the Au−Ag alloy [149]. The simulation results shown in Figure 14b agree with the experimental results concerning the plasmon resonance position.…”
Section: Plasmonic Properties Of Metal Nanoparticles and Plasmon Senssupporting
confidence: 84%
See 1 more Smart Citation
“…where x denotes the Au molar fraction in the Au−Ag alloy [149]. The simulation results shown in Figure 14b agree with the experimental results concerning the plasmon resonance position.…”
Section: Plasmonic Properties Of Metal Nanoparticles and Plasmon Senssupporting
confidence: 84%
“…In this case a dielectric environment (water) where bodies with homogeneous and isotropic dielectric functions are separated by abrupt interfaces is assumed, thus solving Maxwell equations using the boundary conditions at the particle boundaries. As for the dielectric function of the considered Au/Ag alloy, a weighted average method was used, in which the dielectric function of the alloy is defined as: ε alloy ( ω ) = x ε Au ( ω ) + (1 − x ) ε Ag ( ω ) where x denotes the Au molar fraction in the Au−Ag alloy [ 149 ].…”
Section: Promising Applications Of Lal Nanostructures For Biotechnmentioning
confidence: 99%
“…Reproduced with permission. [ 195 ] Copyright 2019, American Chemical Society. g) Surface plasmon resonance sensors for DNA hybridization with graphene WS 2 coatings.…”
Section: Application Of 2d Material‐based Optical Biosensorsmentioning
confidence: 99%
“…For example, Farokhnezhad et al. Studied the optical and photothermal properties of graphene coated gold silver alloy hollow nanoshell and found that it is suitable for a class of excellent photothermal treatment nanomaterials, [ 195 ] as shown in Figure 26d . In the experiment, metal nanoparticles have great photothermal conversion efficiency and excellent optical properties, which are suitable for photothermal therapy.…”
Section: Application Of 2d Material‐based Optical Biosensorsmentioning
confidence: 99%
“…   G is the graphene conductivity, which is defined as the sum of the contributions of interband and intraband transitions according to the Kubo theory [27] …”
Section: Optical Characteristics Of Metal-graphene Nanoparticlesmentioning
confidence: 99%